Identification of glycolysis-related molecular subtypes and prognostic model in intrahepatic cholangiocarcinoma - Yue Wang; Pengxiang Wang; Hui Liu; Haokang Feng; Muzi Cao; Zefan Zhang; Keqiang Rao; Jia Fan; Xiutao Fu; Yunfan Sun (Discover Oncology)
Abstract Background Intrahepatic cholangiocarcinoma (iCCA) is the second most common primary liver tumor, notable for its high heterogeneity. Glycolysis plays a critical role in tumorigenesis, progression, and drug resistance across various malignancies, while the therapeutic implications of targeting glycolysis remain underexplored. This study aims to identify glycolysis-related molecular subtypes, explore their functional heterogeneity, and develop a prognostic model for iCCA. Methods Consensus clustering based on 121 glycolysis-related prognostic genes was performed to classify iCCA patients. Functional enrichment analyses revealed key biological pathways associated with tumor progression. A 9-gene risk model (ALDH1B1, DDIT4, GALE, HK1, HMMR, PGAM1, PGK1, PLOD1, SAP30) was constructed using the Least Absolute Shrinkage and Selection Operator (LASSO) algorithm and multivariate Cox regression analysis. HMMR, a glycolysis-related gene, was further investigated for its clinical significance. Results Two molecular subtypes with distinct survival outcomes (p < 0.001) were identified. Functional analyses further revealed that upregulated genes in the C1 subtype were enriched in hypoxia, TNF-α signaling via NF-κB, p53, and apoptosis pathways. A risk model effectively stratified patients into high- and low-risk groups, with worse survival in the high-risk group (p < 0.001, AUC = 0.76 for 1-year, 0.80 for 3-year). A nomogram incorporating the risk score and clinical factors (γ-GT, vascular invasion, lymph node metastasis) achieved a C-index of 0.793. Finally, we identified HMMR as a candidate prognostic biomarker for iCCA patients. Moreover, HMMR was overexpressed in iCCA and associated with poor prognosis, while its knockdown significantly reduced tumor cell proliferation, migration, and invasion (p < 0.001). Conclusions The glycolysis-based risk model enables precise patient stratification and may facilitate clinical decision-making, while HMMR represents a promising therapeutic target, offering novel insights into iCCA prognosis and treatment.